Enhancing mechanical properties of wire + arc additively manufactured INCONEL 718 superalloy through in-process thermomechanical processing. (15th December 2018) - Xu, Xiangfang; Ganguly, Supriyo; Ding, Jialuo; Seow, Cui Er; Williams, Stewart
Abstract: Wire + arc additive manufacture (WAAM) was applied to produce INCONEL 718 superalloy (IN718) components in a layer by layer manner; further, interpass cold rolling was introduced to generate in-process thermomechanical processing effect during the deposition process. Mechanical testing showed that with rolling applied, the strength of the solution plus aging treated WAAM IN718 was improved from 1056 MPa (unrolled) to 1351 MPa (rolled) which met the wrought standard (1276 MPa), and the material anisotropy was eliminated. The unrolled IN718 featured large columnar grains developing along the building direction, with the length and width as large as 11 mm and 0.8 mm respectively; rolling induced plastic deformation triggered a non-uniform recrystallization upon successive depositions, which produced a recrystallized core with small columnar grains and numerous finely equiaxed grains with the grain size of 12.7 μm. The overall strengthening produced by interpass rolling was attributed mostly (76%) to the rolling induced recrystallization which produced grain size reduction strengthening and created larger grain boundary area to allow more precipitation at the grain boundaries, and partially (24%) due to the improved aging response of the recrystallized grain structure. Graphical abstract: Highlights: Wire + arc additive manufacture (WAAM) was applied to deposit IN718. Microstructure and aging response of WAAM IN718 were studied. Explanation was given to the inferior strength of WAAM IN718 to the forgings. Interpass rolling proved to be effective in enhancing the strength of WAAM IN718.